PENGARUH KEPEMILIKAN INSTITUSIONAL, UKURAN PERUSAHAAN DAN PERSISTENSI LABA TERHADAP KUALITAS LABA PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020-2022 - Lalo, Annas; Emil, Emil (Jurnal Unicorn ADPERTISI, 2025)
The purpose of this study is to examine the influence of Institutional Ownership, Company Size and Profit Persistence on Profit Quality in Food and Beverage Companies Listed on the Indonesia Stock Exchange for the 2020-2022 Period. This study uses a quantitative research approach. The population in this study is all manufacturing industry companies in the Food and Beverage sector on the Indonesia Stock Exchange for the 2020-2022 period". A total of 36 companies, due to limited funds, manpower and time and only 25 companies were used as a sample for this study. Based on the results of the analysis, it can be concluded that Institutional Ownership has a significant effect on the quality of profits in food and beverage companies listed on the Indonesia Stock Exchange in the period 2020-2022; Company size has a non-significant effect on the quality of profits in food and beverage companies listed on the Indonesia Stock Exchange in the period 2020-2022; Profit presence affects the quality of profits in food and beverage companies listed on the Indonesia Stock Exchange in the 2020-2022 period.